Candida in Lower Respiratory Tract Increases the Frequency of Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A Retrospective Case-Control Study - Zuo, Yi-hui; Wang, Wei-qin; Chen, Qi-jian; Liu, Bin; Zhang, Feng-ying; Jin, Xiao-yan; Hang, Jing-qing; Li, Hua-yin; Bao, Zhi-yao; Jie, Zhi-jun; Wang, Gui-fang; Gao, Xi-wen; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: To explore impact of Candida on the acute exacerbation of chronic obstructive pulmonary disease (AECOPD) outcome. Methods: A retrospective, multi-center, case-control study was performed. Patients hospitalized for AECOPD in 25 centers during Jan 2011 – Dec 2016 were enrolled, data including demographic information, conditions during the stable phase of COPD, clinical characteristics of AECOPD and follow-up information within 1 year after discharge were collected. Univariate analysis and binary logistic regression were applied, p < 0.05 was taken as significant. Results: Totally 1103 patients were analyzed, with 644 LTR Candida positive cases and 459 Candida negative controls. Long-term prognosis was significantly different between Candida positive and negative group, including the recurrent AECOPD within 180 days (75.5% vs 6.6%, p < 0.001) and mortality within 1 year (6.9% vs 0.4%, p < 0.001). Univariate logistic analysis showed that LTR Candida isolation was related to higher recurrence rate of AECOPD within 180 days and mortality within 1 year. Binary logistic regression analysis showed that LTR Candida isolation was independently associated with recurrence of AECOPD within 180 days. Conclusions: LTR Candida isolation was associated with worse long-term prognosis of AECOPD and strongly, independently related to higher possibility of recurrent AECOPD within 180 days.